FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KEBIJAKAN HUTANG PERUSAHAAN (Studi Empiris pada Perusahaan Manufaktur yang terdaftar di Bursa Efek Indonesia Tahun 2012-2014) - Ifada, Luluk Muhimatul; Yunandriatna, Yunandriatna (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2017)
Debt policy is one of the most important decisions for the company. It is thus important to figure out the determinants of debt policy. The main purpose of this study is to examine the effect of the size, free cash flow, managerial ownership, dividend policy on debt policy of Indonesian manufacturing public listed firms. Data collected from 195 companies from 2012 to 2014 were analyzed using multiple regression. Current study found that free cash flow and managerial ownership have negative effect on the debt policy. Furthermore, the study also found that dividend policy and company size positively affects the debt policy.